Passage and Survival of Juvenile Salmonid Smolts through Dams in the Columbia and Snake Rivers, 2010–2018. (4th May 2021) - Skalski, John R.; Whitlock, Steven L.; Townsend, Richard L.; A. Harnish, Ryan
Abstract: Minimizing the mortality and migration time of juvenile salmon (smolts) that pass through dams is a long‐standing objective in the pursuit of salmon recovery in the Columbia River basin. We compiled and analyzed 40 acoustic tag studies of juvenile salmonid that were performed between 2010 and 2018 at seven of the eight hydroelectric projects in the Federal Columbia River Power System. We found that the use of nonturbine routes decreased monotonically moving downstream from the Snake River to the main‐stem Columbia River dams and associated mortality differed substantially between the dams in the two rivers. Spillways were the predominant passage route at the main‐stem Columbia River dams. In contrast, passage was more common through the surface weirs and juvenile bypass systems at the dams in the Snake River, which generally provided higher survival. The observed stocks exhibited variable passage behaviors and mortalities, and the estimated probability that an individual would pass through all eight dams in the system without using a turbine route was 0.31, 0.47, and 0.60 for subyearling Chinook Salmon Oncorhynchus tshawytscha, yearling Chinook Salmon, and steelhead O. mykiss, respectively. Although subyearling Chinook Salmon were generally more likely to pass through a turbine route, they also experienced less turbine‐associated mortality than did the other stocks, especially steelhead. Notably, the proportion of smolts that passed through the spillway relative to the proportion of water through the spillway was lowest at Bonneville Dam, the largest and lowermost dam in the system. Bonneville Dam also stood out as having the highest proportion of smolts passing through turbines, but it was among the locations with the lowest rates of turbine‐associated mortality.